(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Gingival enlargement is one of the most cumbersome complications of cyclosporine A. It affects patient’s life style by impairing the appearance and function of masticatory tract. This study was conducted on a sample of Iranian kidney transplant recipients to determine the frequency and risk factors of cyclosporine-induced gingival enlargement. Materials and Methods. A total of 200 kidney transplant recipients (mean age, 39.7 ± 13.2 years) were enrolled in this study. All of the participants were receiving cyclosporine for at least 12 months prior to the study. Factors including age, gender, cyclosporine dose, serum concentration of cyclosporine, duration of immunosuppressive administration, plaque, and gingival indexes were evaluated. Results. Seventy kidney transplant recipients (35%) showed various degrees of gingival enlargement. Serum cyclosporine concentration and the intensity of gingival enlargement (McGraw index) had a significant correlation (r = 0.35, P < .001). Multiple regression analysis revealed an independent association between gingival enlargement and either serum concentrations of cyclosporine and plaque index (P < .05). The other variables failed to show a significant relationship with gingival enlargement. Conclusions. The prevalence of cyclosporine-induced gingival enlargement in our patients seems to be almost greater than the prevalence reported in previous studies. There was a significant relationship between cyclosporine immunosuppressive treatment and gingival overgrowth in Iranian kidney transplant recipients.